Glucose Oxidase/Nano-ZnO/Thin Film Deposit FTO as an Innovative Clinical Transducer: A Sensitive Glucose Biosensor - Naderi Asrami, Padideh; Aberoomand Azar, Parviz; Saber Tehrani, Mohammad; Mozaffari, Sayed Ahmad (Frontiers in Chemistry, 2020)
In the present research, a new biocompatible electrode is proposed as a rapid and direct glucose biosensing technique that improves on the deficiencies of fast clinical devices in laboratory investigations. Nano-ZnO (nanostructured zinc oxide) was sputtered by reactive direct current magnetron sputtering system on a precovered fluorinated tin oxide (FTO) conductive layer. Spin-coated polyvinyl alcohol (PVA) at optimized instrumental deposition conditions was applied to prepare the effective medium for glucose oxidase enzyme (GOx) covalent immobilization through cyanuric chloride (GOx/nano-ZnO/PVA/FTO). The electrochemical behavior of glucose on the fabricated GOx/nano-ZnO/PVA/FTO biosensor was investigated by I-V techniques. In addition, field emission scanning electron microscopy and electrochemical impedance spectroscopy were applied to assess the morphology of the modified electrode surface. The I-V results indicated good sensitivity for glucose detection (0.041 mA per mM) within 0.2–20 mM and the limit of detection was 2.0 μM. We believe that such biodevices have good potential for tracing a number of biocompounds in biological fluids along with excellent accuracy, selectivity, and precise analysis. The fast response time of the fabricated GOx/nano-ZnO/PVA/FTO biosensor (less than 3 s) could allow most types of real-time analysis.